Censorship detected in KG (Kyrgyzstan) - Voidly (2024)
CRITICAL severity censorship detected in Kyrgyzstan. Confidence: 75%. Data sourced from CensoredPlanet.
Censorship Incident ID: KG-2024-0001
Keywords: censorship; KG; censorship; critical